There are no solutions.
Work Step by Step
Considering the equation $3(8x-1) = 6(5+ 4x)$, we can apply operations to both sides of the equation to simplify the equation, isolating the variables on different sides of the equations. First distribute the numbers 3 and 6 to their respective sides of the equation. This creates an expression like: $3(8x) + 3(-1) = 6(5) + 6(4x)$, which simplifies to $24x - 3 = 30 + 24x$. Then, you can subtract $24x$ from both sides, shown by: $24x - 3 -24x = 30 + 24x -24x$. This simplifies to $-3 = 30$ This is not a true statement so there is no solution to this question.